Fabrication of gold nanohybrids modified with antibody and functional dendrimers for targeted photothermal theranostics. Issue 4 (23rd December 2020) - Setiawan, Herlan; Yuba, Eiji; Harada, Atsushi; Aoki, Ichio; Kono, Kenji
Abstract: Targeted theranostics can improve benefits of therapeutics or imaging probes by minimizing the dose and by selective delivery to a target site. For this study, a gold nanorod (AuNR)‐based nanohybrid was designed for efficient cancer treatment and diagnosis. The AuNR was functionalized with polyamidoamine dendrimers having poly(ethylene glycol) and Gd‐DOTA residues to provide biocompatibility and magnetic resonance (MR) imaging properties. Furthermore, trastuzumab was conjugated to the obtained nanohybrids to enhance the delivery performance to HER2‐expressing tumor cells. Fabricated nanohybrids possessed uniform hydrodynamic diameter and showed typical surface plasmon absorption, which is useful to convert light energy to heat for photothermal therapy. Nanohybrids exhibited T 1 ‐weighted relaxation and comparable MR imaging property to that of commercially available MR contrast reagent. In vitro experiments demonstrated that photothermal effects of nanohybrid under near infrared (NIR) irradiation were sufficient to kill 80%–90% of cancer cells. The combination of the targeted nanohybrid and NIR laser irradiation strongly suppressed tumor growth and extended the survival of HER2‐positive SKOV3 tumor‐bearing nude mice. Therefore, fabricated nanohybrids are promising for targeted photothermal therapy and imaging. Abstract : This study combined gold nanorods with a gadolinium contrast agent and antibody to create a multifunctional nanohybrid. This nanomaterial has a homogeneous shape, high stability, and high accumulation to cancer cells to increase the imaging and treatment ability.